Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441445
|View full text |Cite
|
Sign up to set email alerts
|

High power VCSEL devices for free space optical communications

Abstract: High power VCSEL (Vertical-Cavity Surface-Emitting Lasers) as light sources for free space optical communications have been developed. These VCSEL devices have 4, 9, or 16 simultaneously driven spots-similar to a single spot VCSEL and have a single cone-shaped Far Field Pattern (FFP) under high optical output power operations at 10, 20 and 40mW. Since the multi spots are driven simultaneously, these devices have a high optical output power even if the optical output power from each spot is small. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…There are only a few research papers to date specifically on the development of VCSEL arrays for free-space optical links. Our experimental arrays trace their origins to the pioneering work of Yoshikawa et al, in 2005 [ 13 ], wherein the authors demonstrated 3 × 3, 4 × 4, and 5 × 5 850 nm VCSEL arrays emitting cone-shaped beams at 2.5 Gb/s, intended specifically as light sources for free-space data links. In 2009 and 2010, Safaisini et al [ 14 , 15 ] reported 980 nm 28-element arrays with a bandwidth ( f 3dB ) of 7.6 GHz, maximum wall plug efficiency (WPE max ) of ~12%, and maximum optical output power of L max ~150 mW.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…There are only a few research papers to date specifically on the development of VCSEL arrays for free-space optical links. Our experimental arrays trace their origins to the pioneering work of Yoshikawa et al, in 2005 [ 13 ], wherein the authors demonstrated 3 × 3, 4 × 4, and 5 × 5 850 nm VCSEL arrays emitting cone-shaped beams at 2.5 Gb/s, intended specifically as light sources for free-space data links. In 2009 and 2010, Safaisini et al [ 14 , 15 ] reported 980 nm 28-element arrays with a bandwidth ( f 3dB ) of 7.6 GHz, maximum wall plug efficiency (WPE max ) of ~12%, and maximum optical output power of L max ~150 mW.…”
Section: Introductionmentioning
confidence: 58%
“…Figure13. Extracted bandwidth f 3dB versus static optical output power (L) for a reference 980 nm single VCSEL with φ~16 µm (black circles) and for a 980 nm triple VCSEL array with φ~9 µm (red squares).…”
mentioning
confidence: 99%
“…The system was equipped with a diffuser and a reflective surface to shape the output beams from multiple VCSELS into a single pill-box light intensity distribution beam profile. In [6], T. Nakamura et al studied an OWC system based on a high-power 940 nm VCSEL. Dong et al proposed a two-user QAM-OFDMA OWC system using a 940 nm VCSEL array.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, VCSEL has several advantages over LEDs and edge-emitting sources because of its low divergence, high beam quality, circularly symmetric output beam, low-cost fabrication and packaging, and low power consumption. As light sources, high power VCSELs at the wavelength of 0.85 µm have been developed for free-spaceoptical communication [7].…”
Section: Introductionmentioning
confidence: 99%